Paleografi Aksara Pegon - Fika Hidayani (Jurnal Tamaddun : Jurnal Sejarah dan Kebudayaan Islam, 2020)
Abstract: Pegon script is a cultural heritage which is important to learn because in the past, this script was used as a medium to conquer colonialism and a collection of information between Mufti. Moreover, this script was considered a sacred script by the society. This is a method of preachers in spreading Islam more easily that  would be accepted by the society. Paleography helps researchers trace the historical record of the development of Islam in Java, because we can know the written evidence on the stone, metal or other materials. By studying Paleography of Pegon Script, the researchers can track the historical record of the development of Islam based on the origin of the development of the writing.